The Effect of Education Intervention on Knowledge Levels and Consumption Pattern of Breastfeeding Mother with Baby 0-6 Months in Sidorejo Village, Ponjong, Gunungkidul - Fibri, Dwi Larasatie Nur; Hidayah, Allaika Nur; Wijatniko, Bambang Dwi (Indonesian Food and Nutrition Progress, 2025)
Indonesia has 17.3% of pregnant Chronic Energy Deficiency (CED) women who are at risk of CED while breastfeeding because they have poor nutritional status. Therefore, it is necessary to take corrective action to increase their knowledge about breastfeeding patterns to optimize nutritional intake through educational interventions. A quasi-experiment with a pre-test post-test with a control group and food recall 24h interview was employed. The knowledge score of the intervention group increased after the education intervention, while the control group didnot change, and there wasno significant difference (p<0.05)in the final score of the intervention and control group. The results of consumption patterns showed that there were significant differences in protein consumption between the initial and final mean scores in the intervention group (p<0.05), while there wasno significant difference in energy consumption, and in the control group, there wasno significant difference (p<0.05). The final mean of protein and energy consumption had a significant differencebetween the intervention and control groups (p<0.05). The relation of knowledge scores with the patterns of protein and energy consumption isnot related between them (counterclockwise) which means if the level of knowledge is good, an increased pattern of protein and energy consumption is not necessary.